Structure of Forensic Characteristics of Murdering Hostages or Kidnapped Persons (Law and Safety, 2020)
The concept and structure of forensic characteristics of crimes against human life and health have been analyzed. Based on the conducted study, the author has offered to define the forensic characteristics of a crime as the system of information about certain types of crimes with a structure consisting of a set of forensically significant elements that help the fastest investigation of the crime.Studying this issue, we came to the conclusion that the structure of forensic characteristics of the murder of hostages or kidnapped persons is currently insufficiently studied. Accordingly, the purpose of this work is to analyze research and to build a structure of forensic characteristics of the murder of hostages or kidnapped persons. Based on the conducted research, the following elements of the forensic characteristics of the murder of hostages or kidnapped persons have been identified: 1) the method of committing the murder of hostages or kidnapped persons (preparation, commission, concealment); 2) the situation and mechanism of committing the murder of hostages or kidnapped persons (place as part of the material environment, which includes, besides the premises and areas, a set of different items); 3) the subject matter of the crime, the subject matter of criminal encroachment, or, as it is also called, the subject matter of criminal interest; 4) features of committing murders (trace picture); 5) forensic characteristics of the offender (physical, socio-demographic data, etc.); 6) forensic characteristics of the victim.
Keywords: forensic characteristics; contract murder; a hostage; kidnapped person